Meet the Challenge (African Knowledges and the History Publication since the 1970s)
Moderated and judged competition on scientific knowledge between students from Haywood Mission Institute and Wells-Hairston High School.
Keywords: Competition; Education; Scientific Knowledge; Quiz Show